Controlling Photocatalytic Activity by Self‐Assembly – Tuning Perylene Bisimide Photocatalysts for the Hydrogen Evolution Reaction. Issue 46 (26th October 2020) - McDowall, Daniel; Greeves, Benjamin J.; Clowes, Rob; McAulay, Kate; Fuentes‐Caparrós, Ana M.; Thomson, Lisa; Khunti, Nikul; Cowieson, Nathan; Nolan, Michael C.; Wallace, Matthew; Cooper, Andrew I.; Draper, Emily R.; et al.
Abstract: Amino acid functionalized perylene bisimides (PBIs) form self‐assembled structures in solution, the nature of which depends on the local environment. Using a high‐throughput photocatalysis setup, five PBIs are studied for the hydrogen evolution reaction (HER) under a range of conditions (pH and hole scavenger concentration) across 350 experiments to explore the relationship between supramolecular structure and photocatalytic activity. Using small angle X‐ray scattering (SAXS), NMR spectroscopy and ultraviolet‐visible (UV‐vis) absorption spectroscopy, it is shown that photocatalytic activity is determined by the nature of the self‐assembled aggregate that is formed, demonstrating the potential of self‐assembly to tune activity. There is a clear correlation between the presence of charged flexible cylindrical aggregates and the occurrence of photocatalytic H2 production, with UV–vis spectroscopy indicating that the most active structure type has a distinctive form of π‐aggregation which is proposed to enable efficient charge separation across multiple PBI units. Abstract : Self‐assembly is an exciting but underexplored field in photocatalysis. The design of molecular chromophores is common, but less attention is paid to how these building blocks assemble. Using high‐throughput testing and detailed characterization, it is shown how a single set of starting molecules can give rise to profoundly different levels of photocatalytic activity depending on their supramolecular structure.